SOSIALISASI LKM TERINTEGRASI PENDEKATAN KONTRUKTIVISME DENGAN PERMAINAN TTS MODIFIKASI SMPN 38 PADANG - Dewi Devita; Lili Rismaini; Wienda Gusta (Politeknik Negeri Sriwijaya, 2021)
Abstract SMPN 38 Padang is located in a rural area making the atmosphere in this school beautiful and close to nature. This situation is very comfortable and good for students to study in this school. But the environment, of course, is not enough as a factor that should be considered in studying. It needs to be supported by teaching materials that can awaken student motivation in learning, especially in math subjects. From the observations made, the devotional team did not find any slightly different mathematics teaching materials. There are only Student Worksheets compiled by the MGMP team. For that reason, we conducted a socialization of Independent Worksheets mathematics integrated approach to constructivism with a game of Crossword Puzzles modifications in students of class VII SMPN 38 Padang with the aim of improving the understanding and motivation of students learning mathematics. Activities are carried out directly and apply strict health protocols using lecture and question and answer methods. Based on these activities, it can be concluded that socialization was successfully carried out with indicators of the number of participants, the activeness of participants, the achievement of the purpose of the activity, and the achievement of material understanding. The follow-up to this activity is to communicate with teachers in monitoring the use of independent worksheet students. Keywords : self-worksheet, constructivism, crossword puzzle